An integrated framework of green supply chain management implementation - Ghobakhloo, Morteza; Tang, Sai Hong; Zulkifli, Norzima; Mohd Ariffin, Mohd Khairol Anuar (International Association of Computer Science and Information Technology, 2013)
With increase in environmental concerns during the past decade, a consensus is growing that environmental pollution issues accompanying industrial development should be addressed together with supply chain management. Therefore, the greening of the supply chain initiative, as implemented by world-class ISO 14001 certified companies has become an obligation to the environment and to the society itself, obligated mainly by governmental regulations and customer perspective on environmental issues. To facilitate the growth of Green Supply Chain Management (GSCM) some implementation guidelines to help academicians, researchers, and practitioners in better understanding integrated GSCM from a wider perspective is needed. The purpose of this paper is to present and integrated framework of GSCM implementation which is based on the rich body of available literature, including earlier reviews that had relatively limited perspectives. This study will assist different parties involved with greening supply chain processes to achieve a practical synopsis of the GSCM implementation.